Experience and the reality of illusion - Velazquez, Cassidy Garhart, author; Yust, Dave, 1939-, advisor; Sullivan, Patrice M., advisor; DiCesare, Catherine R., committee member; Malpezzi Price, Paola, 1948-, committee member (Colorado State University. Libraries, 2008)
In my paintings I strive to reconcile ambivalent illusions in search of the reality in my own experience. My paintings are narratives about perception and how perception is the product of synchronized inner imaginings and physical experiences. Paint is the perfect medium for this investigation as it allows me to move fluidly between trompe l'oeil and abstract renderings. Both painting approaches are ambivalent in that they represent only themselves and at the same time, in my work, are symbols for something else. In my paintings, trompe l'oeil imagery symbolizes the physical experience and emphasizes how easily perception can be deceived while elements of abstraction attempt to give substance to the inner experience. In between these poles of extreme illusion and non-illusion, I explore the endless realm of referential representation. It is my intention to craft images that function, ambivalently, as both windows and mirrors. As windows, my work offers me, and hopefully others, an ulterior understanding of reality. As mirrors, I endeavor to create, for me and my audience, compositions that echo, literally and metaphorically, the hard and soft edges that also compose a thought-filled life.
Keywords: Art -- Psychology; Optical illusions in art; Painting, American -- 21st century